INTERCULTURAL THOUGTH IN EDUCATION, MUSEUMS, TERRITORIES - Giusti, Mariangela (European Scientific Journal, ESJ, 2013)
This paper reports some results from a research conducted for ten months in 2011 in some cities of northern Italy. This was a qualitative and interdisciplinary research that have been conducted towards forty in-depth interviews with witnesses (men and women) included in the age group 25-40 years, immigrants in Italy for at least five years from different countries of East Europe and several other countries. The research has correlated various subject areas: intercultural pedagogy, museography, adult education, earth sciences, pedagogy of the territory, social education, cultural entertainments. Emerged from the interviews are references to projects based on the principles of intercultural education in some important museums of cities of center and north of Italy: Modena, Reggio Emilia, Bologna, Mirandola, Collecchio, Nuoro. In this paper are given large enough references to projects of various museums intended as opportunities for training, empowerment, social cohesion flanking really the work of schools and teachers in the transmission of a truly intercultural thinking.